Precision measurement of a potential-profile tunable single-electron pump. (5th February 2015) - Bae, Myung-Ho; Ahn, Ye-Hwan; Seo, Minky; Chung, Yunchul; Fletcher, J D; Giblin, S P; Kataoka, M; Kim, Nam
Abstract: We performed a precision measurement of the current from a single-parameter electron pump, where the potential-profile for a quantum dot was manipulated by multiple top-metal gates. In an optimally tuned condition, driven with a sinusoidal-waveform microwave at f = 0.95 GHz, B = 11 T, and T = 0.3 K, the relative deviation of the pump current from ef, δI p / ef ≡ ( I p − ef )/ ef was measured to be (−0.92 ± 1.37) ppm. Our experiment reproduces the current quantisation accuracy of a previous measurement of a single-parameter pump, but in a device fabricated using very different geometry, thereby indicating that accurate single-parameter pumping is insensitive to device details.